Reduced Expression of Eukaryotic Translation Initiation Factor 3 Subunit e and Its Possible Involvement in the Epithelial–Mesenchymal Transition in Endometriosis. (January 2018) - Cai, Xianjun; Shen, Minhong; Liu, Xishi; Guo, Sun-Wei
Epithelial–mesenchymal transition (EMT) is now well documented to be involved in the development of endometriosis through the promotion of invasion and fibrogenesis. To date, several factors have been reported to be involved in EMT in endometriosis. The eukaryotic translation initiation factor 3 subunit e (eIF3e) protein is a component of the multisubunit eIF3 complex essential for cap-dependent translation initiation. The aim of this study was to investigate whether eIF3e is involved in EMT in endometriosis. We recruited 40 premenopausal women (34.7 [6.8] years) with laparoscopically and histologically diagnosed ovarian endometriomas, and their ectopic endometrial tissue samples were collected after informed consent. As controls, endometrial tissue samples were obtained after informed consent from 40 premenopausal women, roughly age-matched (36.9 [6.4] years) and menstrual phase–matched with endometriosis group, who underwent surgery for benign gynecologic disorders or cervical intraepithelial neoplasia but without endometriosis, adenomyosis, or uterine fibroids. All tissue samples were subjected to immunohistochemistry analysis of eIF3e, transforming growth factor (TGF-β1), Snail, E-cadherin, vimentin, and proliferating cell nuclear antigen (PCNA). We found significantly reduced immunoreactivity against eIF3e and E-cadherin but elevated immunoreactivity against TGF-β1, Snail, vimentin, and PCNA in endometriotic epithelial cells when compared to that of control endometrium (all P values <.05). The eIF3e staining levels correlated negatively with that of TGF-β1 and Snail but positively with that of E-cadherin (all P values <.05). These data suggest that eIF3e downregulation may be involved in EMT in endometriosis, possibly through preferential translation of Snail. Future studies are warranted to confirm whether this is the mechanism.